Serogrouping and subtyping of Legionella pneumophila with monoclonal antibodies. - Joly, J R (1983)
Monoclonal antibodies directed against Legionella pneumophila serogroups 1 to 6 were produced by fusing splenocytes of BALB/c mice with the Sp 2/0-Ag14 or the NSO mouse myeloma cell lines. Specificity of these antibodies was determined by indirect fluorescent-antibody staining: 8 reacted with L. pneumophila serogroup 1 and, respectively, 13, 6, 6, 5, and 10 reacted with serogroups 2, 3, 4, 5, and 6; all except 5 were serogroup specific, and none presented cross-reactions with six other species of Legionellaceae. Serogroup determination of 35 isolates of L. pneumophila with seven selected monoclonal antibodies resulted in correct serogrouping in all instances; a pool of the same seven monoclonal antibodies stained intensely all strains of L. pneumophila without any staining of the other species of Legionellaceae. When 24 serogroup 1 isolates of L. pneumophila were stained with eight serogroup 1-specific monoclonal antibodies, the staining patterns could be clustered in five distinct groups. These hybridomas thus represent an unlimited source of standard reagent that could be used in the detection and serogrouping of L. pneumophila; differences in staining patterns could be used as epidemiological markers for these bacteria.